KARAKTERISTIK DAKTILITAS SS304 YANG TEROKSIDASI PADA TEMPERATUR TINGGI - Setiawan, Jan; Sungkono (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
This paper shows changes in hardness, tensile strength and ductility characteristics of SS304. The SS304 was processed by heat treatment at high temperature in atmospheric environment. SS304 is a type of stainless steel with many superior properties used in industry. In this research, a pipe made of SS304 with 30 mm in diameter was cut in transversal direction at 3 mm width to be used as a sample. The samples were processed by heat treatment at 600, 800 and 1000 °C for 1 and 2 hours in atmospheric environment. After the oxidation process, the samples were cooled by natural cooling outside the furnace or quenched in water. Hardness testing and ring tensile testing were done to the high-temperature oxidized SS304. Analyses were done to study changes in hardness, tensile strength and ductility characteristics of SS304 after oxidation process. The results show that hardness escalation occurs mainly for samples that were cooled by quenching in water compared to natural cooling. The highest hardness value was observed for the sample oxidized at 1000 °C for 1 hour and cooled by quenching, where hardness value changed from 281.25 HV before oxidation to 468.00 HV after oxidation. The tensile strength of the samples, however, tend to decrease, while the ductility of some samples tends to increase. Increase in tensile strength followed by increase in ductility occurs for samples oxidized at 600 °C for 2 hours with natural cooling. The tensile strength after oxidation reaches a value of 744.04 MPa with 12.38 % elongation escalation. As a guidance for implementation, SS304 in high temperature oxidation environment should be limited by temperature of 600 °C.